2018
DOI: 10.1021/acsabm.8b00188
|View full text |Cite
|
Sign up to set email alerts
|

Sheet-like Cellulose Nanocrystal-ZnO Nanohybrids as Multifunctional Reinforcing Agents in Biopolyester Composite Nanofibers with Ultrahigh UV-Shielding and Antibacterial Performances

Abstract: The uses of inorganic metal oxide and ZnO nanohybrids as UV absorbers have potential to increase the production of UVprotective textile, which will also overcome the drawbacks of organic molecules and prevent negative impacts on human health and environment. In this work, sheet-like cellulose nanocrystal-ZnO (CNC-ZnO) nanohybrid was successfully developed by one-step hydrothermal method. The obtained CNC-ZnO nanohybrids as UV absorber and antibacterial agents were introduced into biopolyester (poly(3-hydroxybu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 52 publications
1
51
0
Order By: Relevance
“…Owing to the electrostatic interactions between cellulose nanocrystals and zinc oxide, sheet-like CNC-ZnO nanohybrids were successfully developed by a one-step hydrothermal method [ 88 ]. CNCs were prepared by mixing microcrystalline cellulose (MCC) with an acid solution consisting of 90% citric acid and 10% HCl, at 80 °C for 6 h. The final CNC suspension (neutralized with NH 4 OH and washed with distilled water) was added in an aqueous solution of ZnCl 2 containing NaOH as precipitating agent and homogenized at room temperature.…”
Section: Antibacterial Nanocellulose-metal Oxides Hybridsmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to the electrostatic interactions between cellulose nanocrystals and zinc oxide, sheet-like CNC-ZnO nanohybrids were successfully developed by a one-step hydrothermal method [ 88 ]. CNCs were prepared by mixing microcrystalline cellulose (MCC) with an acid solution consisting of 90% citric acid and 10% HCl, at 80 °C for 6 h. The final CNC suspension (neutralized with NH 4 OH and washed with distilled water) was added in an aqueous solution of ZnCl 2 containing NaOH as precipitating agent and homogenized at room temperature.…”
Section: Antibacterial Nanocellulose-metal Oxides Hybridsmentioning
confidence: 99%
“…In addition, FE-SEM images revealed that the morphology of CNC-ZnO nanohybrids varied from nanosheets to flower-like structures depending on the concentration of Zn 2+ ions. The insertion of CNC-ZnO into the PHBV matrix provided it a UV-blocking ability for both UVA (99.72%) and UVB (99.95%) and excellent antimicrobial activity against Escherichia coli and Staphylococcus aureus [ 88 ].…”
Section: Antibacterial Nanocellulose-metal Oxides Hybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…That was due to the introduce of PEG that would destroy the continuous phase structure of the PVA. Therefore, the addition of PEG was an unfavorable effect to the tensile properties of the composite fibers [22,46]. When the content of PEG as high as 70% (PEG/PVA = 7:3), the break tensile strength of the electrospun membranes still as high as 0.8 MPa.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…ZnO owes this popularity to its large bandgap, ease of doping [4] and its relatively large exciton binding energy, 60 meV, evident even at room temperature. While these features make the ZnO system an attractive choice for optoelectronics [5][6][7][8], they also render it an important candidate in photocatalytic, antibacterial and biomedical technologies [9][10][11]. The emission spectra of ZnO nanostructures are sensitive to their shape, size and defect content [8,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%